AI-GENERATED CONTENT AS A TOOL FOR IMPROVING THE LINGUISTIC COMPETENCE OF STUDENTS - Humeniuk, Iryna (Mountain School of Ukrainian Carpaty, 2024)
The article explores the prospects of using artificial intelligence (AI), in particular chatbots based on the GPT technology, to teach language disciplines. The author analyzes the impact of such tools on students’ linguistic competence, as well as the problems and advantages of their use in the educational process. The aim and tasks of the study have led to the use of a set of theoretical, empirical, visual and graphical methods. To determine the degree of understanding of the problem of using artificial intelligence in the study of language-related educational components, the methods of analysis of scientific sources, synthesis, generalization, abstraction, and comparison have been used. To determine the linguistic, structural, and semantic markers of the AI-generated text, the descriptive method and the methods of observation and analysis of student works have been used. To find out the position of students on the problem, the methods of survey and mathematical processing of the results have been used. Visual methods (diagram construction) have been used to visualize the results of the survey. In the context of fulfilling the objectives of the study, the author analyzes modern scientific works in the field of education to reveal the problem of using AI tools within the educational components «Modern Ukrainian Language with a Practicum» and «Ukrainian Language for Professional Purposes.» It has been found that in-depth research in this area has not yet been implemented. The author emphasizes the need for changes in teaching methods for the effective use of AI technologies. Important steps include the introduction of tasks that help students identify errors in AI-generated texts. To this end, the article compiles a list of linguistic, structural, and semantic markers of AI-generated text. The risks associated with the use of AI, in particular, the problems of academic integrity and the possible reduction of students' independence, are also considered.